Relationship between quadriceps angle and hamstring flexibility with knee injuries among weight lifters in Selangor, Malaysia - Teh, Wei Ze (2022)
Background and Objective: There are many potential risk factors for weight lifters to suffer knee injuries. Quadriceps angle and hamstring flexibility are proven risk factors in suffering knee injuries among athletes. However, no study has been performed to examine the association of these two factors with knee injuries among weight lifters. The purpose of this study is to examine the association between quadriceps angle and hamstring flexibility with knee injuries among weight lifters. It is hypothesised that there is an relationship between these two factors with knee injuries among the weight lifters. Methods: 44 participants were recruited. A consent form and demographic data form were provided for the individuals to fill. Then, the participants were required to fill up the Modified Standardized Nordic Questionnaire, which involved occurrence of past knee injuries. Those who fit the inclusion criteria performed two tests, quadriceps angle measurement and sit and reach test. Data was then collected and analysed. Results: Among recreational weight lifters, there is no significant relationship between Q-angle and knee injuries. There is no significant relationship between hamstring flexibility and knee injuries. There is a significant difference between the Q-angle on the dominant and non-dominant side with and without knee injuries. There is no significant relationship between quadriceps angle and hamstring flexibility, except for the Q-angle on the nondominant side among recreational weight lifters with no history of knee injuries. III Conclusion: The study concluded Q-angle and hamstring flexibility have no significant relationship. The study also concluded that relationship between quadriceps angle and hamstring flexibility with knee injuries both not significant. More research needs to be done on the relationship between Q-angle and hamstring flexibility with knee injuries among recreational weight lifters. There is significant bilateral variability between the Q-angle on both legs for weight lifters regardless of injuries